‘Share your experience’. Digital storytelling in English for tourism - María Alcantud-Díaz; Alicia Ricart Vayá; Carmen Gregori-Signes (Ibérica, 2014)
The main purpose of this article is to describe the experience achieved when implementing practical classes of English for Tourism so as to bridge the gap between the professional world of the tourism industry and what students learn at university. In this article we will first introduce the concept of “digital storytelling” (Lambert, 2006; Gregori-Signes, 2008a, 2008b & 2010; Alcantud-Díaz, 2008 & 2011) and briefly describe some of the projects that have already been developed at the University of Valencia as well as the use of digital stories in the promotion of touristy products. We will then argue that digital storytelling can be considered a productive type of activity which fits the demand of the Common European Framework of Reference for Languages (CEFR) with regard to implementing the use of Information and Communication Technologies (ICTs) within the curriculum. Additionally, it helps to improve traditional skills development, mainly speaking and writing along with researching, collaborative tasks and working with computers. Thirdly, we will depict and discuss authentic examples of digital stories produced by undergraduate students registered in the course “Communication in English Language in Tourism I”.